Tandem-L Observation Concept - Contributions and Challenges of Systematic Monitoring of Earth System Dynamics - Tridon, Daniela Borla; Bachmann, Markus; De Zan, Francesco; Krieger, Gerhard; Zink, Manfred; Schulze, Daniel; Moreira, Alberto (International Radar Symposium (IRS), 2017)
Tandem-L is a proposal for a spaceborne L-band SAR mission that aims at the global monitoring of dynamic processes on the Earth. The mission will acquire an enormous amount of data for different applications. These data will be used to provide information concerning biosphere, geosphere, cryosphere, and hydrosphere. Within the scope of this mission, an observation concept has to be developed in order to fulfill all the scientific requirements and clarify the necessary system resources. A sophisticated planning and optimization process has been implemented. It combines the predetermined satellite resources, ground station network, and the scientific requirements to generate an acquisition timeline on individual data take level. The resulting timeline fulfills all requirements for the various scientific applications and can be used to analyze different aspects of the mission, e.g. data volumes and orbit usage are necessary to refine the on-board and ground resources.
DLR Import::2019-04-03